2019
DOI: 10.1108/ajim-04-2019-0097
|View full text |Cite
|
Sign up to set email alerts
|

What prompts users to click on news headlines? Evidence from unobtrusive data analysis

Abstract: Purpose The headlines of online news are created carefully to influence audience news selection today. The purpose of this paper is to investigate the relationships between news headline presentation and users’ clicking behavior. Design/methodology/approach Two types of unobtrusive data were collected and analyzed jointly for this purpose. A two-month server log file containing 39,990,200 clickstream records was obtained from an institutional news site. A clickstream data analysis was conducted at the footpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 58 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Views, likes, comments and replies were suggested to indicate the popularity of social media by Jiang et al. (2019) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Views, likes, comments and replies were suggested to indicate the popularity of social media by Jiang et al. (2019) .…”
Section: Methodsmentioning
confidence: 99%
“…There is a paucity of literature on measuring social media publicity systematically in household waste management. Generally, the popularity of a subscription account on social media could be reflected by user engagement ( Aldous et al., 2019 ), such as views ( Jiang et al., 2019 ), likes ( Ksiazek et al., 2016 ), user-to-user interaction ( Hu et al., 2017 ) and user comments ( Gaenssle and Budzinski, 2020 ). Previous observations indicated that the popularity of a social media post regarding household waste management was related to its publishing time ( Ma and Chen, 2017 ), published title and topics ( Jing and Wei, 2016 ) in attracting the user attention.…”
Section: Introductionmentioning
confidence: 99%
“…The extracted data were based on the titles of the newspaper articles. The rationale for selecting these titles of the newspapers is to present the crux of the content written in the article (Jiang et al, 2019). These headlines though provided limited data yet encompassed the complete picture of the selected articles.…”
Section: Methodsmentioning
confidence: 99%
“…For example, there can be an e-commerce site where a potential consumer arrives on a product page, reads the content, and takes no other action at that time. Another case is a newspaper site where an audience member comes to the site, scans the headlines, reads the article snippets, but takes no other action, such as clicking [126]. In each of these cases, the visit could last several minutes or longer.…”
Section: Plos Onementioning
confidence: 99%